VITAE: Recuperações de objetos de aprendizagem baseada na Web 2.0 - Maria Augusta Vieira Nelson; Lucila Ishitani; Geovália Oliveira Coelho (Universidade Estadual de Campinas, 2012)
Digital materials used in teaching and learning are called learning objects (LO). Traditionally, LOs were developed for use as support materials for teacher. However, they can be used by students or whoever is interested in learning something. LOs can be found in repositories and also on the Web, in teachers and institutions sites. In spite of that, they are not easily found. Repositories address few knowledge fields and few languages. Search engines return a large amount of information that makes it difficult for users to identify relevant LOs to meet their goals. In this context, this paper proposes a new mechanism for LOs retrieval, based on Web 2.0 principles. Among the options for Web 2.0.